Nerve ultrasound in polyneuropathies. Issue 5 (23rd January 2018) - Telleman, Johan A.; Grimm, Alexander; Goedee, Stephan; Visser, Leo H.; Zaidman, Craig M.
ABSTRACT: Ultrasound can be used to visualize pathology in the peripheral nerves of patients with polyneuropathy. Nerve enlargement is the most frequent pathology, but other abnormalities, including abnormal nerve echogenicity and vascularity, are also encountered. This monograph presents an overview of the role of nerve ultrasound in the evaluation and management of both inherited and acquired polyneuropathies. A description of the sonographic techniques and common abnormalities is provided, followed by a presentation of typical findings in different neuropathies. Scoring systems for characterizing the presence and pattern of nerve abnormalities as they relate to different polyneuropathies are presented. Muscle Nerve 57 : 716–728, 2018